A Advanced Life Support vs Basic Life Support: A review - widiyanto, aris; Wardani, Galuh Sindhi; Pramasti, Risa Ardianti; atmojo, joko tri; Darmayanti, Aquartuti Tri (Jurnal Informasi Kesehatan Indonesia (JIKI), 2019)
ALS and BLS are the treatment options that are always taken when finding a cardiac arrest patient outside the hospital. The purpose of this review is to determine the effectiveness of the two emergency treatments that are correct according to the conditions and also their success in reducing mortality. This review was conducted by the author in June - July 2019, by searching databases including PubMed, Google scholar, and open access science direct to find out the potential of eligible studies. In this study it was explained that BLS was more likely to improve the ability of life of patients after being discharged from the hospital and improve the neurological function of patients after the rescue action from cardiac arrest.